2021
DOI: 10.1101/2021.06.29.450133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absolute quantitation of individual SARS-CoV-2 RNA molecules: a new paradigm for infection dynamics and variant differences

Abstract: Despite an unprecedented global research effort on SARS-CoV-2, early replication events remain poorly understood. Given the clinical importance of emergent viral variants with increased transmission, there is an urgent need to understand the early stages of viral replication and transcription. We used single molecule fluorescence in situ hybridisation (smFISH) to quantify positive sense RNA genomes with 95% detection efficiency, while simultaneously visualising negative sense genomes, sub-genomic RNAs and vira… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…Note that among infected cells, the intensity values computed from the images varied over a large range, consistent with strong differences in viral load ( Figs 2C and S2C ). These data are consistent with earlier studies showing that viral infection is driven by a subpopulation of permissive cells in which the virus can replicate at high levels ( Lee et al, 2021 Preprint ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Note that among infected cells, the intensity values computed from the images varied over a large range, consistent with strong differences in viral load ( Figs 2C and S2C ). These data are consistent with earlier studies showing that viral infection is driven by a subpopulation of permissive cells in which the virus can replicate at high levels ( Lee et al, 2021 Preprint ).…”
Section: Resultssupporting
confidence: 92%
“…Several different variations of FISH/smFISH have been developed over the last years ( Pichon et al, 2018 ), and some of them have also been used to visualize SARS-CoV-2 RNA. Commercial solutions include Stellaris RNA-FISH (LGC Biosearch Technologies) ( Lee et al, 2021 Preprint ), HuluFISH (PixelBiotech) ( Stahl et al, 2021 ), RNAscope (ACDBio) ( Liu et al, 2021 ), and hybridization chain reaction smFISH (HCR; Molecular Instruments) ( Acheampong et al, 2021 Preprint ). These methods target specific SARS-CoV-2 RNA regions, such as the S or N gene, or ORF1a.…”
Section: Discussionmentioning
confidence: 99%
“…We detected the RTCs by staining of dsRNA, an intermediate of viral RNA replication. It needs to be mentioned that the amount of genomic viral RNA that is present in infected cells is underestimated by using a dsRNA antibody that indicates only replication factories with high dsRNA content (27). Through volumetric imaging, we confirmed that at least one dsRNA focus is usually associated with the outer layer of an N protein compartment, which might consist of several fused sections.…”
Section: Discussionmentioning
confidence: 53%
“…For viral genomic RNA compared to dsRNA, a stronger colocalization with the N protein would be expected. Using in situ hybridization assays for visualizing viral genomic RNA, Stertz et al (16) for SARS-CoV and Lee et al (27) for SARS-CoV-2 could indeed demonstrate a high co-occurrence of N protein and viral RNA in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other assays, such as expression of a fluorescent protein or RNA sequencing, smFISH is highly sensitive and can be used to detect single mRNA molecules directly upon its synthesis (Femino et al, 1998;Lyubimova et al, 2013). Moreover, smFISH has been used successfully to study the absolute number of viral RNAs and the spatial distribution of viral RNAs of various RNA viruses (Boersma et al, 2020;Garcia-Moreno et al, 2019;Lee et al, 2021;Ramanan et al, 2016;Singer et al, 2021). To validate the RSV smFISH probesets, we infected airway epithelium cells (A549-adenocarcinomic human alveolar basal epithelial cells), reflecting the natural tissue infected by RVS, with human RSV strain A2 and performed smFISH 4 hours post inoculation (hpi) (Fig.…”
Section: Smfish Tools To Explore Early Rsv Gene Expressionmentioning
confidence: 99%